The Use of Folklore E-Books in Introducing Archaic Vocabulary for Elementary School Students - Kusumajanti, Wahju (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study aims to determine the number and meaning of archaic vocabulary in the literacy discourse of the e-book "The Tale of Two Princesses and the King of Snakes", its syntactic aspects, and to introduce archaic vocabulary to elementary school students. The methods used are quantitative and descriptive qualitative. In this discourse, seven archaic vocabularies were found which belong to the category of nouns and adverbs. This research shows that the discourse of children's literacy e-books has been enriched with a variety of vocabulary including archaic vocabulary. With the mastery of language varieties in elementary school children in this digital era, it will enrich their vocabulary, familiarize them to find out, and preserve the Indonesian language.